Efficacy of brief intervention for drug misuse in primary care facilities: systematic review and meta-analysis protocol - Toshi A Furukawa; Yan Luo; Norio Watanabe; Ethan Sahker; Masatsugu Sakata; Rie Toyomoto; Chiyoung Hwang; Kazufumi Yoshida (BMJ Open)
Introduction Drug misuse is associated with significant global morbidity, mortality, economic costs and social costs. Many primary care facilities have integrated drug misuse screening and brief intervention (BI) into their usual care delivery. However, the efficacy of BI for drug misuse in primary care has not been substantiated through meta-analysis. The aim of this systematic review and meta-analysis is to determine the efficacy of BI for drug misuse in primary care settings.Methods and analysis We will include all randomised controlled trials comparing primary care-delivered BI for drug misuse with no intervention or minimal screening/assessment and usual care. Primary outcomes are (1) drug use frequency scores and (2) severity scores at intermediate follow-up (4–8 months). We will retrieve all studies through searches in CENTRAL, Embase, MEDLINE and PsycINFO until 31 May 2020. The reference list will be supplemented with searches in trial registries (eg, www.clinicaltrials.gov) and through relevant existing study reference lists identified in the literature. We will conduct a random-effect pairwise meta-analysis for primary and secondary outcomes. We will assess statistical heterogeneity though visual inspection of a forest plot and calculate I2 statistics. We will assess risk of bias using the Cochrane Risk of Bias Tool V.2 and evaluate the certainty of evidence through the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Sensitivity analyses will account for studies with control group variations and studies with a high risk of bias. If heterogeneity is present, subgroup analyses will consider patient variables of age, sex/gender, race/ethnicity, per cent insured, baseline severity and primary drug misused.Ethics and dissemination This study will use published aggregate data and will not require ethical approval. Findings will be disseminated in a peer-reviewed journal.